Pengaruh Ineffective Monitoring, Personal Financial Need, Ketaatan Peraturan Akuntansi dan Budaya Etis Organisasi terhadap Terjadinya Fraud (Studi Kasus Koperasi di Kecamatan Jembrana) - Dewa Ayu Kade Oka Krisnawati; Putu Riesty Masdiantini (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
Fraud is a deliberate mistake made through fraud, misuse and manipulation to obtain an advantage. This study aimed at examining the effect of ineffective monitoring, personal financial need, compliance with accounting regulations, organizational ethical culture against the occurrence of fraud in cooperatives in Jembrana district. This research employed a quantitative approach. The samples were selected through purposive sampling method with the number of respondents 45 people. The data were collected through questionnaires. The data analysis technique used in this research was multiple linear regression. The results of this study state that (1) ineffective monitoring has a positive and significant effect on fraud, (2) personal financial needs have a positive and significant effect on fraud, (3) compliance with accounting regulations has a negative and significant effect on fraud, (4) ethical culture organization has a negative and significant effect on fraud.